2017
DOI: 10.1038/s41598-017-03943-y
|View full text |Cite
|
Sign up to set email alerts
|

Mahanine exerts in vitro and in vivo antileishmanial activity by modulation of redox homeostasis

Abstract: Leishmania is an obligatory intracellular protozoan parasite responsible for the development of a spectrum of disease manifestation ranging from cutaneous to the more destructive visceral form 1 . Visceral leishmaniasis (VL) is a neglected tropical disease, mainly caused by the species L. donovani, which is prevalent in the Indian subcontinent with 40,000 cases registered each year and 147 million people under the risk 2 . Macrophages are the primary host for the parasite to survive and multiply in the mammali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 52 publications
(64 reference statements)
1
15
0
Order By: Relevance
“…It activated death receptor-induced apoptosis in leukaemia, acts as a mTORC1/2 inhibitor in glioblastoma multiform, Hsp90 inhibitor in pancreatic, enhanced tumor suppressor proteins (PTEN/p53) in colon cancers. Moreover, it showed a synergistic effect with clinically-approved drugs and exhibited immunomodulation 25 32 . Encouraged by these observations, we utilized this pro-oxidant molecule to induce oxidative-stress in OC to understand the interplay between autophagy and anoikis.…”
Section: Discussionmentioning
confidence: 99%
“…It activated death receptor-induced apoptosis in leukaemia, acts as a mTORC1/2 inhibitor in glioblastoma multiform, Hsp90 inhibitor in pancreatic, enhanced tumor suppressor proteins (PTEN/p53) in colon cancers. Moreover, it showed a synergistic effect with clinically-approved drugs and exhibited immunomodulation 25 32 . Encouraged by these observations, we utilized this pro-oxidant molecule to induce oxidative-stress in OC to understand the interplay between autophagy and anoikis.…”
Section: Discussionmentioning
confidence: 99%
“…Mahanine is a carbazole alkaloid isolated from a medicinal plant native to the Indian subcontinent. In vivo studies have shown that mahanine induces apoptosis of both antimony sensitive and resistant L. donovani ( Roy et al, 2017 ). Mahanine augments NO and ROS generation, thereby causing parasitic apoptosis due to oxidative stress.…”
Section: Host-targeted Therapeutics and Approaches For Treatment Of Lmentioning
confidence: 99%
“…Additionally, it showed a good synergistic effect with clinically approved drugs both in colon and cervical cancers. It also exhibited antileishmanial activity through immunomodulation [9].…”
Section: Introductionmentioning
confidence: 99%